Enforcement and Enmeshed Consequences: The Limitations of Conventional Criminal Justice Reform - Shannon A. Cumberbatch (Washington University Journal of Law & Policy, 2016)
This Article, by Shannon Cumberbatch, a criminal defense attorney at The Bronx Defenders, explores the intersection between criminal arrests, engrained police practices, and alternative areas of law in the context of systemic criminal justice reform. Cumberbatch discusses the various legal problems that enmesh arrested individuals. Through the lens of New York City’s enforcement of marijuana laws, Cumberbatch advocates for a holistic approach to criminal justice reform that remedies the punishment and marginalization the system was designed to avoid.
Keywords: criminal arrests; engrained police practices; mass incarceration; holistic approach; criminal justice reform; marijuana laws